2014
DOI: 10.1002/pi.4788
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity properties of expanded graphite-polycarbonatediol polyurethane composites

Abstract: WileyRedondo Foj, MB.; Ortiz Serna, MP.; Carsí Rosique, M.; Sanchis Sánchez, MJ.; Culebras, M.; Gómez, CM.; Cantarero, A. (2015). Electrical conductivity properties of expanded graphite polycarbonatediol polyurethane composites. Polymer International. 64 (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…Different approaches, such as wet techniques, 2 blade-coating, 3 electrochemistry, 4 melting, 5 etc. have been used to modify the doping, 4 fabricate composites, 6 and tailor other characteristics that have been studied for their optimization and to understand how nanostructuring of organic materials affects their thermoelectric performance. Then, two conductive polymers, namely Poly(3,4-ethylendioxitiophene) (PEDOT) and Poly(3-hexylthiophene-2,5-diyl) (P3HT) will be described in detail, showing not only the advances obtained in their thermoelectric performance from a fundamental point of view, gaining a new insight into the behavior of such polymers, but also the implementation of device prototypes which show the potential of these materials.…”
Section: Nanoscale Organic Materialsmentioning
confidence: 99%
“…Different approaches, such as wet techniques, 2 blade-coating, 3 electrochemistry, 4 melting, 5 etc. have been used to modify the doping, 4 fabricate composites, 6 and tailor other characteristics that have been studied for their optimization and to understand how nanostructuring of organic materials affects their thermoelectric performance. Then, two conductive polymers, namely Poly(3,4-ethylendioxitiophene) (PEDOT) and Poly(3-hexylthiophene-2,5-diyl) (P3HT) will be described in detail, showing not only the advances obtained in their thermoelectric performance from a fundamental point of view, gaining a new insight into the behavior of such polymers, but also the implementation of device prototypes which show the potential of these materials.…”
Section: Nanoscale Organic Materialsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] However, considering the different results obtained for several nanocomposite systems, a high number of challenging questions remain unsolved.…”
Section: 25mentioning
confidence: 99%
“…As an example, nanotubes were proven to allow a sufficient level of conductivity to manufacture components with antistatic properties which successfully started to appear in the market [8]. To the best of our knowledge, despite a number of papers dealing with electrical conductivity and percolation of graphene nanocomposites are available in literature [9,10,11,12], only few papers deal with the electromagnetic SE performance of such materials. Lianga and others in [13] studied the EMI shielding effectiveness in X-band (8.2-212.4 GHz) of solution-processable functionalized graphene (SPFG) in epoxy and showed that an interesting SE of -20 dB (which is the minimum value requested in commercial applications, ) can be obtained with 15 wt.% loading.…”
Section: Introductionmentioning
confidence: 98%